Pengaruh Teori Fraud Dalam Mendeteksi Kecenderungan Kecurangan Pengelolaan Dana Desa Dengan Religiusitas Sebagai Variabel Moderasi Pada Desa Di Kecamatan Lumban Julu Kabupaten Toba - Grace Debora Manurung; Duma Megaria Elisabeth; Tri Dharma Sipayung (Jurnal Ilmiah Raflesia Akuntansi, 2025)
This research aims to determine the influence of fraud theory in detecting fraud and misappropriation of foreign funds with religiosity as a variable in the mode of income in Lumban Julu Sub-district, Toba Regency. This type of research is quantitative research using primary data. The population in this research is all village government officials and the sample uses a saturated sample, namely Village Heads, Village Heads, Affairs Heads, Section Heads, Hamlet Heads, in Villages in Lumban Julu District (12 Villages), 80 respondents. The data analysis technique used in this research is descriptive statistics. Primary data quality testing was carried out by conducting validity and reliability tests, classical assumption tests, multiple linear regression tests, hypothesis tests and moderation regression tests using the SPSS 26 application. The results of this research individually showed that pressure had no influence on Fraud Fraud Fraud Management of Government Funds. Opportunities have a negative and significant influence on the risk of fraud in the management of foreign funds. Rationalization has a positive and significant influence on the risk of fraud in the management of foreign funds. Religiosity cannot moderate the relationship between Right, Opportunity, Rationalization and the Risk of Fraud, Management of Foreign Funds